AKIBAT HUKUM BAGI PERUSAHAAN BILA TIDAK MENGIKUTI PENGATURAN UPAH MINIMUM BAGI PEKERJA DI INDONESIA - Hafizha Hasna Afifah (Fakultas Hukum Universitas Muhammadiyah Tapanuli Selatan, 2022)
This study aims to examine the legal consequences for companies that provide wages lower than the applicable minimum wage. Wages are compensation in the form of money which is given based on an agreement or through a work agreement between a worker or laborer and an entrepreneur or employer or based on laws and regulations and is the right of the worker or laborer including benefits for the worker or laborer and their family which is given because of their work. by employers or employers. This means that workers who have carried out the orders or work given are entitled to receive wages from their work. Meanwhile, the minimum wage is the lowest monthly wage. Therefore, the provision of such wages must not be lower than the minimum wages that have been regulated in the statutory regulations. The research method used is juridical normative with a statute approach and a case approach. The results obtained from this research are that the company or employer will get sanctions or penalties if they do not provide wages in accordance with applicable regulations. Keywords: Labor Rights, Because of Law, Wage